A new International Tin Agreement? - Günter Behrendt (Intereconomics, 1985)
The International Tin Council (ITC) has, by setting up a “Preparatory Committee”, once more given the starting signal for the preparation of a new International Tin Agreement (ITA). The intention is that the new agreement should take over from the current 6th ITA when it expires on 30th June, 1987. Presently the Agreement is facing a difficult situation. The apparent equilibrium between demand and supply since the beginning of 1985 remains unstable and some producer countries are urging their governments to leave the ITA. How could this situation come about? How can the problems be solved? *** DIRECT SUPPORT *** A02GP040 00007
Keywords: 330; Raw Materials